Legal Uncertainty Due to Dualism in Land Regimes and the Urgency of Integrating the National Agrarian System - Hermawan Sutanto; Zudan Arief Fakrulloh (Journal Customary Law, 2026)
The dualism of the land regime in Indonesia is a structural problem stemming from the disharmony between agrarian law and forestry law, both of which claim authority over the same object: land. The Basic Agrarian Law constructs land as an object of rights that can be owned, controlled, and registered to ensure legal certainty, while the forestry regime places most of the land area as forest areas under state control through an administrative designation mechanism. This situation creates conditions where certified land can be declared as being in forest areas, thus giving rise to legal uncertainty, agrarian conflicts, and weakening the protection of community rights. This problem also shows that the national agrarian system has not yet functioned as an integrated legal system, both from a normative and institutional perspective. This study aims to analyze the roots of the dualism of the land regime, its implications for legal certainty, and formulate a model for integrating the national agrarian system. The study uses a normative juridical method with a statutory, conceptual, and historical approach. The analysis is conducted on various land and forestry regulations, agrarian legal doctrine, and the concept of state control over land. The research identified that regime dualism results from differences in legal construction, fragmentation of institutional authority, and the absence of a unified land administration system. These conditions have resulted in ongoing agrarian conflicts, obstacles to the implementation of agrarian reform, and weak legal certainty regarding land rights. Reconstruction of the national agrarian system needs to be directed at unifying land administration, harmonizing regulations, integrating national databases, and affirming the agrarian system as a single legal system that provides legal certainty and equitable protection of community rights.